TOXIC RELATHIONSHIP GURU KEPADA SISWA DAN SESAMA REKAN KERJA - Aditya Utami; Cornelia Octamara; Rauly Sijabat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to understand the phenomenon of toxic relationships that occur between teachers and students and fellow co-workers in the school environment. A qualitative approach with a case study method was used to explore the experiences and perceptions of participants through in-depth interviews, observations, and document analysis. The results of the study revealed that toxic relationships between teachers and students are often characterized by authoritarian behavior, verbal intimidation, and lack of empathy, which have a negative impact on students' mental health and learning motivation. Meanwhile, toxic relationships between co-workers arise from internal conflicts, lack of effective communication, and unhealthy competition, which affect the work climate and professionalism in the school environment. This study highlights the importance of emotion management training, interpersonal communication development programs, and school policies that support a healthy work culture to prevent and address toxic relationships in the educational environment.